Behavioral and Morphological Traits of Nellore Cattle That Can Influence Calf Survival and Performance from Birth to Weaning - Paranhos da Costa, Mateus José Rodrigues [UNESP]; Menezes, João Vitor de Toledo [UNESP]; Fernandes, Luane da Silva [UNESP]; Valente, Tiago S. (MDPI, 2023)
This study aimed to identify behavioral and morphological traits of Nellore cattle that can influence calves’ survival and pre-weaning performance. It was performed in two units of a large-scale cow–calf operation farm located in the Central-West region of Brazil, with 975 cow–calf dyads, by scoring cows’ maternal protective behavior, body condition, horns, udder suspension (US), teat size (TS) and calves’ vigor. TS was used to determine teat symmetry (TSm). The production unit where calves were born, their birth date, sex, and birth (BW) and weaning weights were also recorded. Cow ages at calving and production units were used to categorize the cows into twelve classes (Cage). The Shapiro–Wilk test alongside tables of frequencies were used to determine if continuous and categorical variables followed a normal distribution, respectively. Two datasets were considered in statistical analyses: (i) 975 dyad records were used to identify potential factors influencing calf survivability and (ii) 936 records of weaned calves were used to assess pre-weaning performance. Generalized linear models were used to assess the effect of target traits on the calves’ weight adjusted for 210 days of age (W210, kg) and pre-weaning average daily gain (preADG, kg/day). Tukey’s test was used to compare W210 and preADG means. Pearson’s correlation coefficients were estimated between BW, W210 and preADG. Cage, US and the TSm significantly affected pre-weaning calf performance (p < 0.01). Older cows (independently of the production unit) and those with intermediate US and symmetrical teats weaned heavier calves. As expected, positive and significant correlation was observed between BW and preADG (r = 0.35), which, in turn, was highly correlated with W210 (r = 0.99). We concluded that none of the behavioral and morphological traits influenced calf survivability, but cow age, US and TSm impacted pre-weaning performance, with 8- to 11-year-old cows and those with intermediate US and symmetric teats leading to better calf performance at weaning.
Keywords: animal welfare; calf vigor; maternal protective behavior; predators; udder and teat morphology